Redictors of adolescents\' moral behavior based on moral attitude, moral identity, benefit and cost - arezou Delfan Beiranvand; Khosro Rashid; Aboulghasem Yaghobi; rasool Kordnoghabi (مجله علوم روانشناختی, 2023)
Background: The identification of factors that can explain the occurrence of moral behaviors by individuals has been studied by theorists in various studies. However, it is also important to consider why moral behaviors are not performed by people with moral identities and attitudes. Could other factors, such as benefit and cost, play a role as a consequence of moral behaviors in different situations? Aims: In this regard, this study was conducted to investigate the predictors of adolescent moral behavior based on moral attitude, moral identity, benefit, and cost. Methods: The design of this study was descriptive and correlational. The statistical population included all adolescents in the academic year 2021-2022. The sample size consisted of 928 people who were selected by multi-stage cluster random sampling and completed the Moral Behavior Scale (Delfan Beiranvand & Rashid, 2022), Moral Identity (Aquino & Reed, 2002), Moral Attitude (Delfan Beiranvand & Rashid, 2022), and Benefit and Cost Scale (Delfan Beiranvand & Rashid, 2022). Data were analyzed using variance analysis and stepwise regression Results: The results of this study indicated a positive significant relationship between variables of moral identity, moral attitude, situational benefit, and psychological benefit with moral behavior, and a negative significant relationship between situational cost and psychological cost with moral behavior. The results revealed that variables of situational benefit, moral attitude, situational cost, and moral identity were the most important predictors of moral behavior among adolescents, respectively, and these variables could predict 0.25% of the variance of moral behavior (R2= 0/255, R= 0/50). Conclusion: Based on the research findings, it can be said that compared to moral identity and attitude, the degree of benefits and costs that is gained by performing moral behaviors in a situation can play a greater role in predicting moral behaviors. When moral behaviors are associated with more situational benefit and less situational cost, they are more likely to occur by individuals in the situations. The results of this study have significant implications for all organizations.